Violation of the Politeness Principle in the Presidential and Vice-Presidential Debates 2019 Presidential and Vice-Presidential Elections - Kusworo, Andy; Rustono, Rustono; Mardikantoro, Hari Bakti (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Politeness in speaking the presidential and vice-presidential candidates in the 2019 presidential and vice-presidential election debates is an interesting phenomenon to be studied from a pragmatic perspective because social and verbal interactions will appear naturally. The purpose of this study is to analyze and describe the form of violations of the politeness principle according to Leech (2014) committed by presidential and vice-presidential candidates in the presidential and vice-presidential election debates of the Republic of Indonesia in 2019. This study uses a pragmatic approach, namely using the politeness theory proposed by Leech (2014). Data collection techniques using listening and note-taking techniques. The data analysis technique was carried out using normative techniques. The results of this study were found to be violations of Leech's five principles of politeness, namely (1) the thimble of feeling, (2) the thimble of approval, (3) the thimble of humility, (4) the thimble of agreement, and (5) the thimble of opinion.